SEARCH OF MECHANISMS AND FORMS OF COOPERATION INTERACTION IN CHAINS OF DELIVERIES - Arseny V. Brykin (Модернизация, инновация, развитие)
In article features of development of the Russian model of mixed economy and integration of the private, public and state beginnings, and also conditions of financial and economic uncertainty which introduced the additional, difficult operated risks and problems to domestic industrial production are considered. According to the author, in modern conditions, considering external calls and threats, and also internal risks, coordination in cooperation communications is of particular importance. Exactly here the greatest extent of development of cooperation communications and tools of an innovative paradigm of development of business is required. The author gives examples of mechanisms and forms of cooperation interaction in chains of deliveries and offers coordination options in cooperation communications in the conditions of an economic crisis.